2016
DOI: 10.1111/ijfs.13341
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition, cellular antioxidant capacity and antiproliferative activity in mango (Mangifera indica L.) pulp and peel

Abstract: Cellular antioxidant activity (CAA) and inhibition of hepato‐cellular carcinoma (HepG2) proliferation were evaluated for the first time in the pulp and peel of mango cultivars. Comparatively, peel had high flavonoids and tocopherols content and showed significant antioxidant activity. Among all the studied cultivars, the Xiao Tainong peel was predominant with highest fistein, mangiferin and alpha‐tocopherol content and significant cellular antioxidant activity value 2986 ± 380 μmol QE/100 g FW. The HepG2 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
(71 reference statements)
2
32
0
Order By: Relevance
“…Epidemiological studies have demonstrated the significance of phytochemicals, especially phenolic compounds, to human health due to their additive and synergistic effects on radicals scavenging [7][8][9]. Recent years, more studies focused on phytochemical profiles and antioxidant activities of fruits [10][11][12][13][14][15], and also the nuts [16,17], such as walnut [18,19], pistachio [20,21], and chestnut [1,3,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have demonstrated the significance of phytochemicals, especially phenolic compounds, to human health due to their additive and synergistic effects on radicals scavenging [7][8][9]. Recent years, more studies focused on phytochemical profiles and antioxidant activities of fruits [10][11][12][13][14][15], and also the nuts [16,17], such as walnut [18,19], pistachio [20,21], and chestnut [1,3,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, on the other hand, according to many studies, phenolic compounds are accumulated in the epidermal layer (peel) of the fruit at the tissue level (Cevallos‐Casals, Byrne, Okie, & Cisneros‐Zevallos, ). For example, many fruit such as pear, blueberry, apple, citrus, and mango, their peel tissues contain higher quantities of phenolic compounds as compared with flesh (Abbasi et al, ; Hu, Zhang, Ke, Li, & Zhou, ; Kim et al, ; Li et al, ; Vieira et al, ; Wang, Camp, & Ehlenfeldt, ). Previous studies have pointed out that the external concentration of phenolics is involved in protection of plant cells against pathogens and environmental stress (Treutter, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are different groups of biologically active polyphenols in grape pomace, including flavonoids phenolic acids, and condensed tannins (Abbasi et al, ; de Oliveira et al, ; Ye, Sun‐Waterhouse, You, & Abbasi, ). The most common flavonoids found in grapes are anthocyanins and variations in their chemical structures implies their high reactivity during food processing, being highly sensitive to acidity (Putnik, Bursać Kovačević, & Dragović‐Uzelac, ), heat and oxidative degradation (Bursać Kovačević, Putnik, Dragović‐Uzelac, et al, ; Patras, Brunton, O'donnell, & Tiwari, ; Ricci, Parpinello, & Versari, ) therefore their extraction from plant cells is an important task closely associated to the need of preservation their biological activity.…”
Section: Introductionmentioning
confidence: 99%